KOMBINASI HERBISIDA GLIFOSAT DAN AIR KELAPA FERMENTASI DALAM MENGENDALIKAN GULMA DI PERKEBUNAN KELAPA SAWIT MENGHASILKAN - Venti Jatsiyah; Nurhayati Nurhayati; Yulinarti Yulinarti (Journal of Agro Plantation (JAP), 2022)
Young coconut water can be used as a basic ingredient in making herbicide formulas. The purpose of this study was to determine whether the concentration of the herbicide glyphosate and fermented air in controlling weeds in oil palm plantations yielded and to determine the most effective concentration in controlling weeds in oil palm plantations. This study used a Randomized Block Design (RAK) which was arranged in a factorial manner. The first factor is the concentration of the herbicide combination (H) consisting of: H1 = concentration of 2 ml glyphosate + 200 ml fermented coconut water, H2 = concentration of 4 ml glyphosate + 100 ml fermented coconut water. The second factor is the dose given (D), namely: D1 = 0.2 l/8 m2, D2 = 0.4 l/8 m2 and D3 = 0.6 l/8 m2. Each treatment was repeated 3 times. The data obtained were analyzed statistically by Analysis of Variances (ANOVA). If it has a significant effect, it will be continued with Duncan's Multiple Range Test (DMRT) at the 5% level. The results showed that the use of a combination of the herbicide glyphosate and fermented air was effective, the most effective concentration in controlling weeds in oil palm plantations resulted in a concentration of 2 ml glyphosate + 200 ml fermented young coconut water.